Estimation of Stature from Percutaneous Length of Tibia in Natives of Gujarat (Medico Legal Update, 2020)
The Indian Constitution guarantees equal right of justice, life and liberty to all Indian citizens. Every personhas freedom of expression (unlawful act committed upon him/her) and it remains when the person died byany mean. Identification of an individual is primary element to investigate both civil and criminal cases.With the time, complexity of crime advance and forensic experts’ role become very crucial in investigationof crime. Crime investigation become very difficult and crucial when investigation agency find unknownmutilated body, bundle of bones or parts of bone. Without identification of dead person, investigation ofcrime become directionless. Key factor for identification are age, sex and stature. Many factors should betaken in to consideration to fix stature with help of bone. Many researchers had been clearly proved thatlong bone can be uses to estimate stature and it depend on race, ethnic and region. Very less work had beendone to formulate regression formula from tibia in state of Gujarat. This study aims at formulate a regressionformula to estimate stature from percutaneous length of tibia (PCTL) for native of Gujarat. This study wascarried out in Department of Forensic Medicine, C.U. Shah Medical College, Surendranagar, Gujarat. Total800 (400 male & 400 Female) undergraduate MBBS student between 18 to 25 years of age were participatedin study. Their stature and percutaneous length of tibia were estimated with standard method and manner.Results are analysed and studied. Results show that there is highly significant in mean length of tibia andstature in both male and female participants (P